TATBIQ ISTIRATIJYAH TAKLIMUL AQRON FI TADRIS QAWAIDUNNAHWI AL ARABI FIL MADRASATIL ALIYAH AL HUKUMIYAH AL ISLAMIYAH ASSANIYAH LOMBOK AL WUSTO - Idris Idris (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
This study aims to evaluate the implementation of peer tutoring learning strategies in teaching Arabic grammar (nahwu) at Madrasah Aliyah Negeri 2 Lombok Tengah, West Nusa Tenggara. The research method used is a qualitative approach with a descriptive type. Research data were collected through observation, interviews, and document analysis to explore the effectiveness of the implementation of this strategy. The results of the study indicate that the implementation of peer tutoring strategies has a positive impact on student motivation and involvement in the learning process. Students who act as tutors show an increase in understanding the material because the peer teaching process strengthens their mastery of concepts. Conversely, students who become tutor participants feel more comfortable asking questions and discussing, thus accelerating their process of understanding the rules of nahwu. In addition, the collaborative atmosphere created during learning increases students' self-confidence and social skills. Peer tutoring strategies also help teachers overcome learning challenges, such as limited time to provide individual attention to each student. This study has implications for the recommendation of peer tutoring strategies as an innovative alternative in Arabic language learning that can be widely applied to support student learning outcomes.